Pengaruh Pelatihan Dan Komitmen Kerja Terhadap Kinerja Pegawai Pada Kantor Balai Pengembangan Penjaminan Mutu Pendidikan Vokasi Bidang Kelautan, Teknologi Informasi Dan Komunikasi (BPPMPV-KPTK) Gowa - Irfan, Andi; Jumaidah; Alfian, Yusri Izha Mahendra (Jurnal Online Manajemen ELPEI, 2024)
This research aims to determine the influence of training and work commitment on employee performance at the Gowa Vocational Education Quality Assurance Development Center Office, Information and Communication Technology (Bppmvp Kptk). The method used in this research is a quantitative method with the number of respondents being 56 employees who were used as samples using a sampling technique, namely probability or random sampling using the sloving technique, where the data collection technique uses a questionnaire. The analysis used in this research is a multiple linear regression test. Simultaneous Test Results Work Experience and Training Variables Have a Positive and Significant Influence on Employee Performance Variables which are Proven Based on Simultaneous Test Results with a Significance Value of F<Α (0.000<0.05). Partial Test Results for Work Experience Variables Have a Positive and Significant Influence on Employee Performance Variables with a Significance Value of F<Α (0.000<0.05) Partial Test Results for Training Variables Have a Positive and Significant Influence on Employee Performance with a Significance Value of F<Α (0.000< 0.05)